Facies variations in gravelly cyclic steps deposited from turbidity currents: Miocene fan delta front deposits compared with a modern active fan delta, central Japan - Takeshi Nakajima; Yoshiki Saito (The Depositional Record)
Abstract Gravelly cyclic steps formed by turbidity currents have recently been widely recognised in the geological record. However, the comparison between modern and ancient gravelly cyclic steps remains challenging. In this study, the facies variations of gravelly cyclic steps deposited from turbidity currents in an outcrop of Miocene fan delta front deposits in central Japan are compared with the geomorphic evolution of analogous cyclic steps on the active fan delta front in modern geological systems. These cyclic steps share common characteristics in setting, grain size and dimensions, allowing direct comparison between ancient and modern examples. Repeat bathymetric surveys of the modern Kurobe River fan delta have revealed various types of upslope migrating bedforms interpreted as cyclic steps. Most of these are short‐lived due to erosion of thalwegs by powerful surge‐type turbidity currents triggered by slope failures or burial of thalwegs by deposition, possibly from river‐fed hyperpycnal flows. Such erosion and burial events occur annually on the fan delta front, resulting in compensational cycles. Sedimentary facies of the Miocene fan delta front deposits include conglomerate with a gently upslope dipping erosional base, backset‐stratified sandstone and foreset‐stratified sandstone, which are interpreted as deposits of hydraulic jumps in high‐density turbidity currents in scours on the stoss sides of cyclic steps. Parallel‐stratified conglomerate sandstone is an additional component. Although previous facies models of gravelly cyclic steps have focussed on deposits on stoss sides, a comparison of modern and ancient examples suggests that facies on the lee sides could be parallel‐stratified conglomerate sandstone and undulating bedforms, reflecting supercritical flow conditions. The present study also suggests that hyperpycnal and surge‐type high‐density turbidity currents may deposit different types of facies and play different roles in the construction and destruction of cyclic steps. The present study has significant implications for facies models of gravelly cyclic steps.